Heat transfer augmentation in Rib-Roughened Narrow channels with one-sided heating - Islam, M. Serajul; Monde, M.; Hino, R.; Huq, A.M.A.; Mohiuddin, A. K. M. (1997)
Heat transfer and frictional pressure drop performance in a very narrow rectangular channel having one-sided constant heat flux input and repeated-ribs for turbulent flow with water as the working fluid have been investigated experimentally and their emperical correlations were obtained using the least-square method. The rib pitch-to-height ratios (p/k) were 10 and 20 while holding the rib height constant at 0.2 mm. The experiment was performed with different Reynolds number (Re) at two channel heights of 1.2 mm and 3.2 mm, the rib height-to-channel equivalent diameter (k/De) of 0.03 and 0.09, respectively. The results show that the rib-rouoghened surface augments heat transfer by about 2-3 times compared with the smooth surface at the expense of 2.8-4 times higher frictional pressure drop under a wide range of Re = 2,414 to 98,458, at p/k = 10, and H = 1.2 mm. Experimental results obtained at channel height, H = 1.2 mm show slightly higher heat transfer and friction factor performance than the higher channel height, H = 3.2 mm.